O pioneirismo de Alberto Guerreiro Ramos nos estudos sobre hierarquias raciais : a gênese de uma formação discursiva pós-colonial - Cruz, Leonardo Borges da (2015)
The thesis presented here aims to point to studies by sociologist Alberto Guerreiro Ramos about relationships (or hierarchies) race in the decades 1940- 50, demonstrating aspects (themes, methods, categories of analysis) developed in postcolonial studies. I follow an initial hypothesis that the writings of Guerreiro Ramos constitute black thought. So I will try to show how models that inspired the author - especially phenomenology and existentialism - were mobilized in the preparation of statements of very authentic and original way. However, the context in which he produced his study of race relations was the affirmation of a way of thinking which Guerreiro Ramos little or scarcely converged. He was taking notes and incorporating that knowledge came from the blackness of the African diaspora, the process of African decolonization and other foreign references as well as debates on Brazilian development. Keep that to the extent that these mergers happened he found it difficult to read a perspective that he himself does not seem to be fully aware, namely that he operated a locus of enunciation interstitial, constituting what Hall called decentered subject.